Influence of Parmigiano Reggiano Diet on Male Sexual Behavior in Rats: Behavioral and Neurochemical Study - Di Viesti,; G. Carnevale,; M.M. Carrozzo,; M. Zavatti ,; M. Baraldi, (Journal of Pharmacy and Nutrition Sciences, 2012)
The influence of Parmigiano Reggiano (P.R.) cheese on copulatory behavior was studied in male rats. Sexually naїve, sluggish and potent rats were chronically fed with a diet of P.R. cheese for 10 d. Mount, intromission, ejaculation latencies and the percentage of mounting and ejaculating animals were recorded during the mating test. Microdialysis technique was used to detect the extracellular levels of dopamine (DA) and its metabolite dihydroxyphenylacetic acid (DOPAC) in rat brain following the P.R. diet. The P.R. diet was able to improve sexual behavior in naїve rats increasing the percentage of mounting and ejaculating animals. Moreover it was able to reduce latencies of mounts, intromissions and ejaculations and to increase the percentage of mounting and ejaculating animals in sluggish rats. Finally, in the microdialysis study an increase in DA and its metabolite DOPAC was found in P.R. fed naїve rats in comparison with control group.